Perlindungan Hukum terhadap Pelaku Aborsi Berdasarkan Kedaruratan Medis menurut Undang-Undang Nomor 17 Tahun 2023 tentang Kesehatan dan Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana - Candra Rahma Dhani; Sartika Dewi; Muhamad Abas (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines legal protection for abortion actors in medical emergency cases under the Health Law, the 2023 Criminal Code and Government Regulation 28/2024. The main issue lies in the gap between the normative recognition of lawful abortion exceptions and the risk of criminalization when procedure, gestational limits, or medical proof are not fulfilled. Using normative juridical method, this study finds that patients and medical personnel are protected when the abortion is based on lawful indications, performed in authorized facilities and supported by consent and medical assessment. Operational guidelines remain necessary to prevent criminal interpretation.